3D-printed dermis-specific extracellular matrix mitigates scar contraction via inducing early angiogenesis and macrophage M2 polarization - Lei Chen (KeAi Communications Co., Ltd., 2022)
Scar contraction frequently happens in patients with deep burn injuries. Hitherto, porcine dermal extracellular matrix (dECM) has supplied microenvironments that assist in wound healing but fail to inhibit scar contraction. To overcome this drawback, we integrate dECM into three-dimensional (3D)-printed dermal analogues (PDA) to prevent scar contraction. We have developed thermally gelled, non-rheologically modified dECM powder (dECMp) inks and successfully transformed them into PDA that was endowed with a micron-scale spatial structure. The optimal crosslinked PDA exhibited desired structure, good mechanical properties as well as excellent biocompatibility. Moreover, in vivo experiments demonstrated that PDA could significantly reduced scar contraction and improved cosmetic upshots of split thickness skin grafts (STSG) than the commercially available dermal templates and STSG along. The PDA has also induced an early, intense neovascularization, and evoked a type-2-like immune response. PDA's superior beneficial effects may attribute to their desired porous structure, the well-balanced physicochemical properties, and the preserved dermis-specific ECM cues, which collectively modulated the expression of genes such as Wnt11, ATF3, and IL1β, and influenced the crucial endogenous signalling pathways. The findings of this study suggest that PDA is a clinical translatable material that possess high potential in reducing scar contraction.